Ethnic Consciousness in B.P. Koirala’s Sumnima - Kandel, Bhanubhakta Sharma (Crossing the Border: International Journal of Interdisciplinary Studies, 2014)
B. P. Koirala’s Sumnima is more criticized as a Freudian Nepali fiction but it is more than that. The novel is a very beautiful and important gift of the novelist to the practitioners of cultural theory because the novelist has discussed the issues of minority, plurality of meaning in cultural practices, cultural differences and ethnic consciousness through the innocent characters, among others. It also documents the conflict and problems among the people living in the same area and helps us understand the value of respecting the other. The book has talked in favour of the weaker section of the society and has made the indigenous practices and way of life victorious through the use of environment, vernacular language, characters, life style, beliefs, norms and values, art, myth, etc. over the classic living style guided and prescribed by the shashtras. Sumnima is a great documentation of cultural reconciliation among the people of different ethnic origins following different beliefs, norms, values and cultural practices. DOI: http://dx.doi.org/10.3126/ctbijis.v2i1.10810 Crossing the Border: International Journal of Interdisciplinary Studies Vol.2(1) 2014: 23-30